The Ability to Understand Repeat Words of Fifth Grade Students at Negeri Karang Elementary School - Yuliningsih Yuliningsih (Universitas Sebelas Maret, 2022)
The aim of the research is to describe the ability to understand repeat words of fifth grade students at SD Negeri Karang. The reseach method. The population is 30 students in class v SD Negeri Karang . The data collection technique uses the test methode. Based on the results of analysis, it can be concluded that the ability to understand repeat words of Class fifth students at SD Negeri Karang is a good. This is proven good.The achievement of an overall average score in the test reaching 83.